Surabaya Menuju Kota Ramah Lansia: Peluang dan Tantangan - Deshinta Vibriyanti (Jurnal Kependudukan Indonesia, 2018)
Increasing number of the elderly globally and nationally has broad implications in family, community and state. WHO issued an age-friendly cities guideline to respond two demographic phenomena, namely aging population and high levels of urbanization. To maintain the quality of health, the elderly need both physical and social environments that consider their characteristics and needs. This facilitates the elderly to access the services, interact with others and actualize themselves optimally. This study aims to analyze the opportunities and challenges faced by Surabaya as one of the ageing population city in Indonesia to be an age-friendly city. Data was collected through quantitative and qualitative approaches. The quantitative approach use several secondary data at the provincial and city levels such as the 2016 Susenas data, 2017 and the 2015 Sakernas. The qualitative approach include interviewing stakeholders, observing, and reviewing literature. This study concludes that Surabaya has an opportunity to be an age-friendly city. This is because Surabaya has local regulation that support fulfillment of elderly need, the existence of elderly institution, and the committed local leader to support the eldery. However, there are still many challenges faced by the Surabaya City, particularly related to inadequate physical facilities, housing, and employment opportunities for the elderly. It requires commitment and support from all elements of the city, public and private sector.Â